The Impact of Organizational Intelligence on the Performance of Tehran Municipality Utilizing Marketing Capabilities - Hashemzehi, Mitra (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this study is to explore the impact of organizational intelligence on the performance of Tehran Municipality through the utilization of marketing capabilities. Methodology: This qualitative study was conducted in Tehran and utilized semi-structured interviews with senior managers, department heads, and key personnel within the Tehran Municipality. Participants were selected through purposive sampling based on their extensive experience and knowledge related to organizational intelligence and marketing. Data were collected until theoretical saturation was achieved, ensuring a comprehensive understanding of the topics. Thematic analysis was used to identify patterns and relationships within the data, with findings validated through member checks to ensure accuracy and credibility. Findings: The analysis revealed four main themes: Organizational Intelligence, Marketing Capabilities, Performance Improvement, and Impact on Municipality. Key subcategories included strategic planning, decision-making, knowledge management, innovation, resource optimization, market research, branding, digital marketing, customer engagement, service innovation, public relations, efficiency, service delivery, employee performance, financial management, strategic alliances, public satisfaction, community development, economic growth, policy implementation, and innovation adoption. The findings underscored the importance of integrating organizational intelligence and marketing capabilities to enhance strategic planning, decision-making, innovation, and overall municipal performance. Conclusion: The study concludes that the integration of organizational intelligence with marketing capabilities significantly enhances the performance of Tehran Municipality. Strategic planning, decision-making, knowledge management, and innovation are crucial components of this integration.